The Effects of CON Repeal on Medicaid Nursing Home and Long-Term Care Expenditures - David C. Grabowski; Robert L. Ohsfeldt; Michael A. Morrisey (SAGE Publishing, 2003)
Certificate-of-need (CON) and construction moratorium laws are used widely by states as a potential mechanism for constraining Medicaid nursing home expenditures. However, there is only limited empirical work examining whether these policies are effective at lowering Medicaid spending. Using aggregate state-level data from 1981 through 1998, this study found that states that repealed their CON and moratorium laws had no significant growth in either nursing home or long-term care Medicaid expenditures. In the context of declining occupancy rates within the nursing home market, this study provides strong evidence that states have little to fear in terms of increased expenditures with the repeal of CON and moratorium laws.